Ars Moriendi. Ethical Challenges of the Ultimate Realities of Life - Sgarlata, Sara; Dłużewicz, Alicja; Napiwodzka, Karolina (ETHICS IN PROGRESS, 2022)
The aim of this issue of Ethics in Progress is to provide a provisional, open-ended view on the ultimate realities of life and the ethical challenges they pose in medical, sociological, and existential contexts. The issue explores axiologies and meta-ethical narratives related to the art of dying, or in other words the moral domain encompassing the quest for a good life and a good death. Two problematic aspects emerge from the latest body of research: (1) the difficulty involved in tackling ethical challenges in medical and sociological contexts; and (2) the marginal role of the patient’s agency and narrative-ownership of end-of-life decision-making. A direction is pointed out that suggests that interventions across interdisciplinary groups involved in medical aid to dying should focus on promoting ethical behaviour on the side of healthcare personnel. Finally, attention to language, discourse, communication, and the narratives of death and dying call this edition of Ethics in Progress to examine the ontological and epistemological categories that underlie the study of lifeworlds and ‘discourse communities’, which are those associated with moral agents interlacing historical motives, language, communication, normative beliefs, social norms and roles, power relations, hard clinical evidence, and contested values in the context of medical practices and, broadly speaking, practices surrounding death.